(untitled) (International Journal of Food and Nutritional Sciences, 2022)
While the world is raising voice for and against the global debate on artificial intelligence, witnessing financial crisis in major economies of the world and political cards playing dull, the discussion about start-ups as the boon and bane have grown stronger for Indian economy.